Identifying concerns and needs in AYA survivors of pediatric cancer: a scoping review - Moura, Maria Jesus; dos Santos, Margarida Custódio; Barros, Luísa (Frontiers in Psychology, 2025)
BackgroundAdolescent and young adult survivors of pediatric cancer (AYA-CCS) require specialized, age-appropriate care throughout their lives. This scoping review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) to identify and map self-reported difficulties, concerns, and needs among AYA-CCS.MethodsA comprehensive search was conducted in PubMed, Scopus, Web of Science, and EBSCOhost (PsycINFO and CINAHL) for articles published between 2014 and 2024. Eligible studies included first-person data from AYA-CCS (aged 15–39 years), addressing their cancer-related difficulties, concerns, or needs. Studies using qualitative, quantitative, or mixed methods were considered. Two reviewers independently screened studies and resolved discrepancies through discussion.ResultsWe screened 1,247 records, of which 24 studies met the inclusion criteria. The findings were classified into two main dimensions: (1) Concerns, including psychological burden, long-term effects, infertility and its impact on relationships, transition of care, fear of recurrence, and social, professional, and financial challenges; and (2) Needs, including tailored information, psychological support, and communication challenges.ConclusionThis scoping review highlights the multiple challenges faced by AYA-CCS, with emphasis on psychological burden. Survivors report needs related to information, psychological support, and communication. Flexible, age-adapted psychoeducational approaches may be beneficial. Involving survivors in program design could enhance relevance. Stratified research by age or developmental stage is essential to align care with evolving needs. A lack of standardized AYA-CCS definitions was identified, underscoring the need for uniform criteria to strengthen future research and care.